Age-wise and gender-wise prevalence of oral habits in 7–16-year-old school children of Mewar ethnicity, India - Pradeep Vishnoi; Prabhuraj Kambalyal; Tarulatha Revanappa Shyagali; Deepak P Bhayya; Rutvik Trivedi; Jyoti Jingar (Indian Journal of Dental Sciences, 2017)
Objectives: The study aimed to check the age- and gender-wise prevalence of oral habits in the children of 7–16-year-old Indian children. Materials and Methods: A cross-sectional survey involving 1029 (661 males and 368 females) children of age 7–16 years was done to record the presence or absence of the oral habits with the aid of the anamnestic questionnaire. The recorded oral habits were tongue thrusting, thumb or digit sucking, mouth breathing, bruxism, lip biting or lip sucking, and nail biting. The collected data were subjected to Pearson's Chi-square statistical analysis to know the overall difference in the prevalence rate of different oral habits and to evaluate the gender- and age-wise difference in the prevalence of oral habits. Results: Oral habits were present in 594 participants (57.73%). The highest prevalence rate was registered for tongue thrusting habit (28.8%), which was followed by nail biting (201/19.5%) and thumb sucking (128/12.4%), mouth breathing (109/10.6%), lip biting (85/8.3%), and bruxism (29/2.8%). The male participants showed a greater prevalence rate for the oral habits than the female participants (58.55% vs. 56.25%). There was a significant difference in the age-wise prevalence of oral habits with older children showing greater prevalence of oral habits than the younger ones. Conclusion: The prevalence of oral habits in the current group of children is high. It warrants the need for the community-based educational preventive and interceptive programs to spread the awareness regarding the deleterious effects of these oral habits.